Prevalence of Risk Factors of Cerebrovascular Diseases in Hospitalized Patients (Journal of Chittagong Medical College Teachers' Association, 2018)
Background: Stroke is one of the foremost causes of morbidity and mortality in Bangladesh. It has diverse risk factors. The present study is aimed to observe the common risk factors of stoke in our perspective. Materials and methods: This observational study was conducted for a 1 year period (April 2010 to March 2011) on 100 patients of stroke admitted in different medicine units of Chittagong Medical College Hospital. Different risk factors were identified along with clinical features after diagnosis of stroke of 100 patents. After collection, data were analyzed and presented to find out demographic pattern, clinical presentation and association with different irreversible and modifiable risk factors. Results: Among the 100 patients of stroke age distribution revealed most of the stroke patients were age group 51-60 years (58%) next to which was 61-70 years (22%). Male was 68 (68%) and female 32 (32%). Male to female ratio was 2.1:1. Among the all study patients most were doing business (22%) and engaged in service (20%). Majority of women were housewife (28%). Regarding type of stroke, 82 (82%) cases were ischemic and 18 (18%) were hemorrhagic type of stoke. Regarding analysis of risk factor of stroke hypertension (62%) was found to be the most common risk factor. Next to which was smoking (54%) followed by DM (28%) and heart disease (24%). Conclusion: From the above findings we can conclude that Hypertension, Cigarette smoking, Diabetes mellitus and Ischemic heart disease are the major risk factor of stroke in our setting.JCMCTA 2017 ; 28 (2) : 12-15